AN APPROACH TO JOSE MARTI’S PHILOSOPHICAL THOUGHT - Chávez Rodríguez, Justo A (Atenas, 2012)
Jose Marti’s philosophical thought is a speech that flows along all his work. His conceptions of nature, man, thought are of paramount importance in his thought. His philosophical thought identifies the practical character and his adiption to culture